Population forecast of Anhui province based on the GM(1, 1) model. Issue 1 (6th February 2017) - Gao, Hong; Yao, Tianxiang; Kang, Xiaoru
Abstract : Purpose: The purpose of this paper is to predict the population of Anhui province. The authors analyze the trend of the main demographic indicators. Design/methodology/approach: On the basis of the main methods of statistics, this paper studies the tendency of the population of Anhui province. It mainly analyzes the sex structure and the age structure of the current population. Based on the GM(1, 1) model, this paper forecasts the total population, the population sex structure, and the population age structure of Anhui province in the next ten years. Findings: The results show that the total population was controlled well, but there have been many problems of the population structure, such as the aging population, high sex ratio, heavy social dependency burden, and the declining labor force. Social implications: This paper forecasts the main indexes of the population of Anhui province and provides policy recommendations for the government and the relevant departments. Originality/value: This paper utilizes data analysis method and the grey forecasting model to study the tendency of the population problems in Anhui province.